'It's all considered to be unacceptable behaviour': Criminal justice practitioners' experience of statutory housing duty for (ex)offenders. (December 2016) - Cooper, Vickie
Despite a growing recognition of the intersectional relationship between homelessness and incarceration, we have a limited knowledge about housing policy and practice for people leaving custody and (ex)offender groups in the community. Addressing these gaps, this paper provides an overview of the main local housing authority statutory duties in the provision of housing support for prison leavers and (ex)offenders in England and Wales, and situates the issues with accessing accommodation within the wider context of austerity. The paper presents a case study that explores criminal justice practitioners' experiences of working with local authority housing agencies. Stemming from 25 interviews with housing practitioners and criminal justice practitioners, the paper outlines the main challenges facing criminal justice agencies as they try to secure accommodation for homeless (ex)offenders and resettle them in the community. Finally, the paper concludes by raising critical questions about the housing options for this population, now and in the future.